2023
DOI: 10.1021/acs.jpca.2c07531
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigations on the Plasmon-Mediated Dissociation of Small Molecules in the Presence of Silver Atomic Wires

Abstract: Plasmonic nanoparticles can promote bond activation in adsorbed molecules under relatively benign conditions via excitation of the nanoparticle's plasmon resonance. As the plasmon resonance often falls within the visible light region, plasmonic nanomaterials are a promising class of catalysts. However, the exact mechanisms through which plasmonic nanoparticles activate the bonds of nearby molecules are still unclear. Herein, we evaluate Ag 8 −X 2 (X = N, H) model systems via real-time time-dependent density fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 54 publications
1
21
0
Order By: Relevance
“…The significant overlap of H 2 antibonding orbitals with Ag states allows for the external laser to drive charge to excited states and then couple to the antibonding H 2 state, driving dissociation. In a separate study using the LC-ωPBE functional, H 2 was found to activate readily even with small amounts of charge transfer from linear Ag chains …”
Section: Mechanistic Studies Of Lspr-induced Reactionsmentioning
confidence: 94%
See 1 more Smart Citation
“…The significant overlap of H 2 antibonding orbitals with Ag states allows for the external laser to drive charge to excited states and then couple to the antibonding H 2 state, driving dissociation. In a separate study using the LC-ωPBE functional, H 2 was found to activate readily even with small amounts of charge transfer from linear Ag chains …”
Section: Mechanistic Studies Of Lspr-induced Reactionsmentioning
confidence: 94%
“…In a separate study using the LC-ωPBE functional, H 2 was found to activate readily even with small amounts of charge transfer from linear Ag chains. 71 To gain mechanistic insight into plasmon-mediated N 2 dissociation, RT-TDDFT was used with a variety of longrange corrected and GGA functionals to study the interaction of N 2 with linear Ag chains (n = 4, 6, 8). 13 It was found that N 2 π* hybridization with Ag σ orbitals provided a path for plasmon-mediated charge transfer.…”
Section: Reactionsmentioning
confidence: 99%
“…They found that the N 2 molecule gained a greater degree of activation when the longitudinal excitation mode was excited compared to the charge-transfer and transverse excitation modes . Hull and Aikens then compared N 2 and H 2 activation/dissociation when these adsorbates interact with Ag n systems . The orientation of small molecules on the nanowire was compared and the parallel orientation was found to lead to a greater degree of charge transfer between the wire and the N 2 and H 2 molecules, which can aid the dissociation of the adsorbate.…”
Section: Introductionmentioning
confidence: 99%
“…43 Hull and Aikens then compared N 2 and H 2 activation/dissociation when these adsorbates interact with Ag n systems. 44 The orientation of small molecules on the nanowire was compared and the parallel orientation was found to lead to a greater degree of charge transfer between the wire and the N 2 and H 2 molecules, which can aid the dissociation of the adsorbate. Both adsorbates were found to pick up electron density early in the dissociation process, with N 2 accommodating more additional electrons than H 2 , even though H 2 was found to dissociate more readily than N 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The electric field is applied along the z axis (Figure ), and the strengths of the fields were chosen to be 0.01 au (3.57 × 10 14 W/cm 2 ), 0.005 au (1.79 × 10 14 W/cm 2 ), and 0.001 au (3.57 × 10 13 W/cm 2 ), respectively. The electric fields were chosen based on a previous work that shows very weak activation of H 2 (coupled with an Ag 8 nanowire) with a CW electric field strength of 0.001 au and slightly stronger activation for 0.01 au . Electric fields were applied in both the positive z ( Z +) and negative z ( Z −) directions, which correspond to the maxima of the CW fields.…”
Section: Introductionmentioning
confidence: 99%